Microbiological Aspects of Ethylene Oxide Sterilization: III. Effects of Humidity and Water Activity on the Sporicidal Activity of Ethylene Oxide - Kereluk, K. (1970)
An investigation determined the effects of environmental moisture content or water activity (Aw), exposure humidity, and sterilant concentration on the resistance of microbial spores. Decimal reduction values [expressed as D values at 54.4 C-specified concentration (milligrams per liter) of ethylene oxide] were determined from spore destruction curves of Bacillus subtilis var. niger dried on hygroscopic and nonhygroscopic surfaces. Four groups of spore preparations were preconditioned in one of four Aw environments (<0.1, 0.1, 0.5, 0.95) for 2 weeks or longer and were exposed to 500 mg of ethylene oxide per liter at 54.4 ± 3 C and 10, 50, and 95% relative humidity in a specially designed thermochemical death rate apparatus. A fifth group did not receive any preconditioning treatment and was exposed immediately after preparation, in the same apparatus at the same temperature, to ethylene oxide concentrations of 200, 400, 600, 800, and 1,200 mg/liter and relative humidities of 15, 30, 50, 60, and 90%. The resistance of the spores on both types of surfaces to ethylene oxide increased proportionately with the Aw of the conditioning environment. The study also showed that moisture in the exposure system was not as critical a variable as the ethylene oxide concentration. The spore destruction rates, irrespective of the carrier types at all concentrations and at different humidities, varied little from one another. The decimal reduction values were reduced as the ethylene oxide concentration increased, and no optimal exposure humidity concentration was observed.